Perception of seropositive puerperal about conducts to prevent vertical transmission of HIV (Research, Society and Development, 2022)
HIV-positive mothers face great psychological suffering, they carry with them the fear of their child being contaminated with the virus and the possibility of their own finitude. This article aimd, To know the perception of seropositive puerperal women about preventive measures against vertical transmission of HIV. This is an integrative literature review carried out in the database on Nursing (Bdenf) e Scientific Electronic Library (Scielo), aplplying the Descriptors in Science of Health (DeCS): HIV/AIDS; post childbirth; postpartum women with HIV; Postpartum HIV control; Assistance. At the end of the research, 3 articles met the eligibility criteria and were selected to compose the study. After content analysis, three thematic categories emerged: 1) Reflections on the importance of health promotion and education for the prevention of vertical transmission of HIV; 2) Feelings of postpartum women regarding the reception and the infiasibility of breastfeeding; 3) Realizing the importance of nursing care for health promotion and control of vertical transmission of HIV. It was noticed that nursing care is essential in terms of health promotion, as well as the control and prevention of vertical transmission of HIV. Welcoming and comprehensive care was seen as a tool that has contributed to greater satisfaction and security for postpartum women.